2021
DOI: 10.1007/s00586-021-06726-2
|View full text |Cite
|
Sign up to set email alerts
|

Spine surgery in pregnant women: a multicenter case series and proposition of treatment algorithm

Abstract: Purpose Spinal diseases requiring urgent surgical treatment are rare during pregnancy. Evidence is sparse and data are only available in the form of case reports. Our aim is to provide a comprehensive guide for spinal surgery on pregnant patients and highlight diagnostic and therapeutic aspects. Methods The study included a cohort of consecutive pregnant patients who underwent spinal surgery at five high-volume neurosurgical centers between 2010 and 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Changes in normal physiology during pregnancy may lead to the complexity of LBP. LBP during pregnancy may be related to increased levels of relaxin, biomechanical changes, weight gain and sagittal imbalance [ 15 ], but in this study, persistent post-cesarean low back pain was associated with the weight of the baby and not with the anesthetic technique.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Changes in normal physiology during pregnancy may lead to the complexity of LBP. LBP during pregnancy may be related to increased levels of relaxin, biomechanical changes, weight gain and sagittal imbalance [ 15 ], but in this study, persistent post-cesarean low back pain was associated with the weight of the baby and not with the anesthetic technique.…”
Section: Discussionmentioning
confidence: 79%
“…It is known that low back pain is common among pregnant women. It occurs in more than 50% of pregnant women [ 15 ], and some patients experience LBP after CS under spinal anesthesia [ 14 ]. When a symptom of LBP persists for more than 6 months after CS, it is known as chronic or persistent LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical guidance from a committee of the American College of Obstetricians and Gynecologists recommends continuous intraoperative fetal heart rate monitoring only when the fetus is viable and an emergency cesarean delivery is possible [ 7 ]. In addition, previous case series of spine surgery on pregnant women have reported that continuous fetal heart rate monitoring is not generally performed in surgeries before the 20th week of gestation, because abnormal heart rate patterns cannot be assessed using continuous fetal heart rate monitoring until about 24 weeks of gestation [ 8 ]. Therefore, in the present case, we planned to monitor the fetal heart rate intermittently with ultrasound Doppler instead of continuous intraoperative fetal heart rate monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The current hypothesis dictates that nearly all of the common drugs used in anesthesia can be safely used after the period of organogenesis, but detailed drug safety studies during pregnancy are lacking [14].…”
Section: Discussionmentioning
confidence: 99%
“…Regional anesthesia decreases the risk of failure to intubate and aspiration, in addition to reducing the exposure of fetuses to potentially teratogenic drugs. However, previous studies have failed to show either anesthetic technique to be superior regarding fetal outcomes [14]. Numerous studies have shown that most drugs can have teratogenic properties at certain doses and at certain times of pregnancy [15].…”
Section: Discussionmentioning
confidence: 99%